1996
DOI: 10.1007/bf02331392
|View full text |Cite
|
Sign up to set email alerts
|

The G-cells in the dog: a light and electron microscope immunocytochemical study

Abstract: An immunohistochemical study has been performed to analyse the distribution of gastrin cells in the gastrointestinal tract of the dog. This study revealed that G-cells immunoreactive for gastrin were almost exclusively present in the pyloric antral mucosa, mainly in the middle third of the pyloric mucosa. The calculated number of G-cells per surface unit area was 8.5 x 10(3)-1.2 x 10(4) cells cm-2. Some gastrin-immunopositive cells were found in the first 10 mm of the proximal duodenum, mainly in the villous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…We have observed that some postembedding immunocytochemical methods, which involve the incubation of sections in sodium metaperiodate and sodium borohydride solutions before immunolabeling (Lobo et al 2000a), result in chromatin bleaching. However, the immunogold methods used in other studies that included the use of sodium metaperiodate but not sodium borohydride (Galán et al 1996;Lobo et al 1997;Goldstein et al 1999) provide an electron-dense contrast to chromatin masses. This observation led us to develop new procedures as simple and reproducible staining methods for the cell nucleus and other cellular structures.…”
mentioning
confidence: 99%
“…We have observed that some postembedding immunocytochemical methods, which involve the incubation of sections in sodium metaperiodate and sodium borohydride solutions before immunolabeling (Lobo et al 2000a), result in chromatin bleaching. However, the immunogold methods used in other studies that included the use of sodium metaperiodate but not sodium borohydride (Galán et al 1996;Lobo et al 1997;Goldstein et al 1999) provide an electron-dense contrast to chromatin masses. This observation led us to develop new procedures as simple and reproducible staining methods for the cell nucleus and other cellular structures.…”
mentioning
confidence: 99%